PEMERATAAN AKSES PENDIDIKAN ISLAM PERSPEKTIF SOSIOLOG: META ANALISIS PENDEKATAN EMILE DUREKHEIM, MAX WEBER, GEORGE HERBERT MEAD, LOUIS ALTHUSSER, DAN IBNU KHALDUN - Mubarak, Fadhil (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam Universitas Islam Malang, 2023)
The problem of inequality in the distribution of education in Indonesia is the cause of obtaining quality and learning opportunities. This causes a difference in the quality of education and the chances of future success. This article aims to analyze various views of sociologists regarding the issue of educational equity, specifically by using the approach of Emile Durekheim, Max Weber, George Herbert Mead, Louis Althusser, and Ibn Khaldun. This research is a meta-analysis of social problems using approaches from various social theories. Data is taken from library sources as primary data in the form of articles from scientific journals and related books. Document analysis procedures were used in data collection. The data analysis technique uses the meta-analysis model. The process of implementing research is carried out on related documents. The results of the research show that Durkheim views that education must create social unity and form the same values ​​throughout society. Meanwhile, Weber believes that access to education must be regulated fairly and everyone has the same opportunity to access it without the influence of economic factors. Meanwhile, Mead views that education has the ability to understand yourself and shape yourself to be able to interact with society. Louis Althusser on the other hand argues that education should be able to maintain elite power and control society. It is different with Ibn Khaldun who views that the education system must be adapted to the conditions and needs of the local community.